KONSEKWENCJE WPISU DÓBR NA LISTĘ UNESCO – PRESTIŻ I CO DALEJ? Postulaty de lege ferenda w zakresie prawnych konsekwencji wpisania obiektu na Listę UNESCO - Ewelina Kowalska (Ochrona Dziedzictwa Kulturowego)
In Poland there are 70 facilities recognised as monuments of history, 14 of which are listed on the UNESCO World Heritage list. From the point of view of the effects in terms of national recognition for the historical monument, it has a prestigious meaning. Given the distinction of cultural monuments as a separately governed issue by article. 7 of the Polish Act on Antiques’ Protection and Care, a question is raised debating the ratio legis of this institution. The possibility to apply for entry onto the UNESCO list is the only result of this legal regulation. However, what is the most problematic – the entry of such historic monument onto this exclusive List also does not constitute a change in terms of the legal status of such an object. The aim of this paper is to analyse the issue of the real and effective judicial protection of, both historic monuments as well as the facilities included in the list of World Heritage.